A molecular‐beacon‐based asymmetric PCR assay for detecting polymorphisms related to folate metabolism. Issue 8 (15th May 2020) - Peng, Qi; Liao, Shengbin; He, Yuejing; Liang, Liyun; Su, Xiaohua; Rao, Chunbao; Li, Wenrui; Li, Siping; Lu, Xiaomei
Abstract: Background: Polymorphisms (rs1801133 or C677T; rs1801131 or A1298C) of the MTHFR gene and rs1801394 (A66G) of the MTRR gene are important genetic determinants of folate metabolism. A convenient, sensitive, and reliable method is required to detect polymorphisms for the precise supplementation of folate. Methods: A rapid detection method based on molecular beacon probes that can detect rs1801133, rs1801131, and rs1801394 simultaneously was developed in this study. Specific primers and probes were designed, and the amplification system and conditions were optimized. We applied our method to a group of 500 unrelated women of gestational age in the Dongguan region of Guangdong Province in China. The clinical performance of this assay was evaluated by testing 94 samples in comparison with Sanger sequencing. Results: The molecular‐beacon‐based PCR assay we established is extremely sensitive, with a detection limit of 2 ng/μL of genomic DNA, and validated by direct sequencing in a blind study with 100% concordance. Conclusion: The results demonstrate that our molecular‐beacon‐based asymmetric PCR assay is an easy, reliable, high‐yield, and cost‐effective method for the simultaneous detection of three polymorphisms related to folate metabolism. It could help evaluate the risk of perinatal‐neonatal neural tube malformation, pregnancy hypertension, and other diseases and guide the individualized supplementation of folic acid. Data on the spectrum of mutations in the Dongguan District in this study are beneficial for guiding the supplementation of folic acid.